Upgrading of pyrolysis bio-oil through hydrodeoxygenation and cracking in a continuous packed-bed catalytic reactor - Gholizadeh, Mortaza (Curtin University, 2015)
Biomass is the only renewable resource that can be used to produce liquid fuels. The pyrolysis of biomass produces a crude bio-oil liquid. This study investigated the catalytic hydrotreatment of bio-oil to produce advanced liquid biofuels. The study focused on the understanding of reaction mechanisms for the formation of light fuel species and solid coke. The results will be useful for the development of low-emission biofuel technologies using non-food lignocellulosic biomass resources.